Teaching preposition by using scavenger hunt game - Retno Rahmawati; Syaprizal Syaprizal; Yulfi Yulfi (Journal of English Language and Pedagogy, 2020)
This research aimed to find out the effectiveness of teaching preposition by using Scavenger Hunt Game to the eighth grade students of SMP Negeri 11 Lubuklinggau in academic year 2019/2020. There are two hypothesis in this research, the null hypothesis (Ho) which stated that it is not effective to teach preposition by using Scavenger Hunt Game to the eighth grade students of SMP Negeri 11 Lubuklinggau and the alternative hypothesis (Ha) which stated that it is effective to teach preposition by using Scavenger Hunt Game to the eighth grade students of SMP Negeri 11 Lubuklinggau. The pre-experimental method was applied in this research. There were 28 students treated as the sample of the research taken from class VIII.3 by using cluster random sampling. The data was collected by writing test. Moreover, the writer used SPSS 20 to analyzed the data. The data from the test was analyzed through individual score, comparison for Minimum Mastery Criteria (MMC), and used ready match t-test. From the data analyse, the writer found out that there was different between the students’ score before and after the treatment. The average score of pre-test was 47.68 and for the post-test was 75.89. Moreover, the result of match t-test was higher than the coefficients of t-table. The result of match t-test was 18.488 whereas the coefficients critical value of t-table was 1.703 for significant level 0.05 for df 27. It means that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. In other word, it was significantly effective to teach preposition by using Scavenger Hunt Game to the eighth grade students of SMP Negeri 11 Lubuklinggau in academic year 2019/2020.